Uterine perforation during hysteroscopy - A. R. Bagdasaryan; S. E. Sarkisov (Опухоли женской репродуктивной системы)
Uterine perforation (UP) is the most common intraoperative complication during both diagnostic and operative hysteroscopy. According to the data obtained by different authors, the rate of UP ranges from 0,13 to 0,76 %. UP undetected timely during diagnostic or operative hysteros- copy is a special hazard: a physician, generally a novice physician, sometimes assesses inadequately the risk of surgical intervention and therefore overlooks UP, by continuing the performance of an already complicated operation, thus aggravating the severity of its consequences.